2017
DOI: 10.1097/pec.0000000000000739
|View full text |Cite
|
Sign up to set email alerts
|

Acute Focal Bacterial Nephritis Associated With Central Nervous System Manifestations

Abstract: Acute focal bacterial nephritis (AFBN) is a localized bacterial infection of the kidney presenting as an inflammatory mass without frank abscess formation. In children, most patients with AFBN present with nonspecific conditions, such as fever, vomiting, and abdominal pain. A small number of reported cases are accompanied by neurological symptoms, including meningeal irritation, unconsciousness, and seizures. We experienced 2 rare cases of AFBN associated with central nervous system lesions. The first case was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The most remarkable difference between the patient groups was that CRP was significantly higher in the MERS with AFBN group. This result corroborated previous case reports of MERS with AFBN (Table 4) [7][8][9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most remarkable difference between the patient groups was that CRP was significantly higher in the MERS with AFBN group. This result corroborated previous case reports of MERS with AFBN (Table 4) [7][8][9].…”
Section: Discussionsupporting
confidence: 92%
“…Various infectious agents have been associated with MERS, among which viruses are the most common [5]. In recent years, several cases of MERS with acute focal bacterial nephritis (AFBN), a localized bacterial infection of the kidney presenting as inflammatory masses without obvious abscesses [6], have been reported in children [7][8][9]. At least 2-3 weeks of antimicrobial therapy tailored to urinary pathogens is recommended for patients with AFBN [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…We also diagnosed AFBN using abdominal contrast CT. Urinary B2MG and NAG are useful markers for the diagnosis of urinary tract infections [15]. Previous reports have also shown that urinary B2MG and/or NAG are useful markers for the diagnosis of AFBN with and without pyuria [4,7,16]. Therefore, we suspected AFBN based on the high levels of urinary B2MG.…”
Section: Discussionmentioning
confidence: 92%
“…Okamoto et al [12] reported MERS with a febrile urinary tract infection due to Klebsiella pneumoniae, and Kometani et al [6] reported two cases of MERS associated with AFBN caused by Enterococcus faecalis. Kasuga et al [7] reported a case of MERS with AFBN caused by E. coli. In this study, E. coli was identified in two of the three cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation